Isolation of actinomycetes from marine ecosystem and study of their bioactive component production potential - H.K. PATEL,; H. N. PATEL,; H.K. PANCHAL,; U. R. DESAI, (International Journal of Pharma and Bio Sciences, 2017)
Antibiotics are generally isolated from microbes, used as antimicrobial and antitumor agents against pathogenic bacteria, fungi and tumors. In present study, nine isolates of Actinomycetes were isolated using spread plate method on Starch Casein Agar (SCA) plates from seven marine water samples collected from Tithal Beach, Valsad. They were used to perform screening for the production of bioactive compounds i. e., antibiotics. These bioactive compounds present in the supernatant were tested against four test organisms. Antibacterial activities were performed using Nutrient Agar (NA) plates by Agar Diffusion Assay with the test organisms. Bioactive compounds were extracted from the supernatant by using two solvents, ethyl acetate and methanol. From the antimicrobial assay, A2 was selected for further study because; it shows good antibacterial activity on Nutrient Agar plate. Mutations were carried out with both physical and chemical mutagens for A2 isolate. A2 was found potential producer of bioactive compound/s.